PENGARUH PELAKSANAAN TRAINING WORK INSTRUCTION TERHADAP PRODUKIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PULP (WOOD PREPARATION 2) PADA PT. INDAH KIAT PULP AND PAPER RIAU PERAWANG - Parulian, Daniel; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the effect of the implementation of the training work instruction on the productivity of the production employees (wood preparation 2) PT. Indah Kiat Pulp and Paper Perawang. Training work instruction as an independent variable (X) has formulated the stages of implementation of activities, tools used, or the parameter referenced standards, testing and inspection. While employee productivity as the dependent variable (Y). This study was conducted on all employees Wood Preparation 2 PT.Indah Kiat Pulp and Paper Perawang as many as 92 people.Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS 17.The results showed that the test results of hypothesis testing t 8.263 t count> t table 1,987. This shows that the work instruction Training affect the level of employee productivity. The amount of work instruction Training effect on employee productivity in the Wood Preparation 2 PT. IKPP Perawang amounted to 43.1%.Keywords: training work instruction, employee productivity